CHARACTER EDUCATIONAL MANAGEMENT (a case study in the Elementary School Penyengat Island) - Raja Suzana Fitri; Makruf Akbar; R. Madhakomala (Program Pascasarjana Universitas Negeri Jakarta, 2018)
This study aims to find out and get an idea of character education management (a case study in the Elementary School Penyengat Island). This study used a qualitative approach to the method used in the form of case studies. The data used in this study are primary and secondary data sources, where researchers use people and documents as data sources. Data collection techniques used in the research were observation and interviews. Data analysis techniques in the study include data reduction, data presentation, and conclusion / verification. Based on the research results as follows: 1) For the planning of moral education in primary schools Penyengat Island has gone well from the aspect of curriculum planning, teaching staff and infrastructure. 2) For the organization of moral education in Penyengat has gone well from the aspects of organizing the curriculum, teaching staff and infrastructure. 3) For the implementation of character education in Penyengat been running with good views of aspects of the implementation of the curriculum, teaching staff, facilities, and student character education in public primary schools Penyengat Island. 4) For the supervision of moral education in Penyengat been running with good views of oversight of curriculum, teaching staff, facilities, and student character education in public primary schools Penyengat Island. Keywords: management education, character education, manners, Penyengat Island